ECTHR_COMMITTEE 19741/23 vom 2. April 2026 , AFFAIRE BADI ET BOULAKSIL c. FRANCE - Ecthr Committee (2026)
Non-violation de l'article 2 - Droit à la vie (Article 2-1 - Vie) (Volet matériel); No violation: 2;2-1